ANALYSIS OF THE EFFECT OF FTSE 100, NIKKEI 225, AND DOW JONES INDUSTRIAL AVERAGE ON COMPOSITE STOCK INDEX IN INDONESIA STOCK EXCHANGE - Suwardi, Suwardi; Amri Mokoginta, Agus (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This study aims to analyze the effect of FTSE 100, Nikkei 225, and Dow Jones Industrial Average on Composite Stock Index in Indonesia Stock Exchange (IDX). The research method used is a quantitative method with time series data type and secondary data obtained the Indonesia Stock Exchange (IDX) website and Bloomberg Data Terminal. The sampling technique used purposive sampling method with monthly data and research period from January 2015 to December 2019. The data analysis technique used is multiple linear regression with normality test, classic assumption test (multicollinearity test, autocorrelation test) and t-statistical hypothesis and f-statistic to test the simultaneous effect with a significance level of 5%. The results of this study indicated that. DJIA Index and FTSE 100 Index variable shows a positive effect and significant to Composite Stock Index and Nikkei 225 Index variable partially has shown a negative effect and significant to Composite Stock Index. Then simultaneously independent variable DJIA Index, Nikkei 225 Index, and FTSE 100 Index together had a significant relation to the dependent variable Composite Stock Index. The determination coefficient of this study indicates the number 87% shows that independent variable variations in DJIA Index, Nikkei 225 Index, and FTSE 100 Index can explain the fluctuating of the dependent variable in Composite Stock Index by 87%. While the remaining of 13% influenced by other independent variables.